Maternal Smoking during Pregnancy Is Associated with Offspring Hypodontia. (August 2017) - Al-Ani, A.H.; Antoun, J.S.; Thomson, W.M.; Merriman, T.R.; Farella, M.
Little is known about environmental risk factors for hypodontia. The objective of this study was to investigate the association between hypodontia and common environmental risk factors, such as maternal smoking and alcohol and caffeine consumption during pregnancy. Eighty-nine hypodontia cases with 1 or more missing permanent lateral incisors and/or 1 or more missing premolars were enrolled in this clinic-based case-control study. Some 253 controls with no missing teeth were frequency matched to cases by age and sex. Hypodontia was diagnosed using panoramic radiographs. Sociodemographic data were collected from both the participants and their mothers, with maternal self-reported active and passive smoking, as well as alcohol and caffeine consumption during pregnancy, assessed by a questionnaire. Odds ratios (ORs) and their 95% confidence intervals (CIs) were calculated with logistic regression to assess the strength of association between risk factors and hypodontia. OR estimates were then adjusted for possible confounders, such as maternal age at delivery, sex and gestational age of the child, and household socioeconomic background. Significant associations were found between hypodontia and maternal cigarette use during pregnancy, as well as the number of cigarettes smoked per day. The consumption of 10 or more cigarettes per day during pregnancy was associated with greater odds of having a child with hypodontia (adjusted OR, 4.18; 95% CI, 1.48–11.80; P = 0.007). Observed associations between hypodontia, second-hand smoke, and alcohol and caffeine consumption were not statistically significant. Maternal smoking during pregnancy is associated with hypodontia. Larger samples and prospective observational study designs, however, are needed to investigate this association further.